2018
DOI: 10.1177/0379572118760373
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Vitamin B Intakes of Zambian Preschool Children: Evaluation of 24-Hour Dietary Recalls

Abstract: All median vitamin B intakes were inadequate among these young children in rural Zambia. Future researchers and policy makers may need to consider B vitamin status in resource-poor areas of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Analysis of the 24-h dietary recalls indicated that women in this study had high prevalence of inadequate intakes for all B-vitamins. In earlier evaluations among children from eastern Zambia, 24-h food recall data [54,55] suggested risk for B-vitamin deficiencies due to high prevalence of inadequate intakes [56]. These evaluations were conducted on 3–5 year old children in 2010 [54] and 5–7 year old children in 2012 [55], allowing B-vitamin intake comparisons over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the 24-h dietary recalls indicated that women in this study had high prevalence of inadequate intakes for all B-vitamins. In earlier evaluations among children from eastern Zambia, 24-h food recall data [54,55] suggested risk for B-vitamin deficiencies due to high prevalence of inadequate intakes [56]. These evaluations were conducted on 3–5 year old children in 2010 [54] and 5–7 year old children in 2012 [55], allowing B-vitamin intake comparisons over time.…”
Section: Discussionmentioning
confidence: 99%
“…These evaluations were conducted on 3–5 year old children in 2010 [54] and 5–7 year old children in 2012 [55], allowing B-vitamin intake comparisons over time. Intake had increased overtime, but percent adequate intake never surpassed 40% [56]. The low intakes of B-vitamins in Zambian women and children are a concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women of child‐bearing age in urban and rural Cambodia and in Vancouver, Canada, were found to have high prevalence of high activity coefficients of erythrocyte glutathione reductase (Whitfield et al., ), an indication of poor riboflavin status. Furthermore, riboflavin dietary intake assessment of Zambian children (Titcomb, Schmaelzle, Nuss, Gregory, & Tanumihardjo, ) and women of child‐bearing age (Kaliwile et al., ) were found to be inadequate in the majority of those evaluated. This is particularly alarming because breastfed children of riboflavin‐deficient mothers are at increased risk of deficiency due to reduced breastmilk concentrations (Allen, ).…”
Section: Riboflavin (Vitamin B2)mentioning
confidence: 99%
“…Surveys in low‐income countries on availability in the food supply and dietary intake suggest that supply and intake are not adequate to maintain B 6 status. A majority of a cohort of rural Zambian children was found to have inadequate B 6 intakes in 2010 and 2012 (Titcomb et al., ), which correlated with low serum PLP, a functional biomarker of vitamin B 6 deficiency, in 79% of the 2012 cohort (Mondloch et al., ). Poor maternal vitamin B 6 status is associated with increased risk of orofacial clefts in newborn children (Munger et al., ).…”
Section: Pyridoxine (Vitamin B6)mentioning
confidence: 99%